IMPLEMENTASI PEMBELAJARAN VIRTUAL DALAM MENINGKATKAN KREATIFITAS ANAK DI MASA PANDEMI DI PIAUD BIRRUL WALIDAIN TAKERAN MAGETAN - Rulik Endarwati (Jurnal Paradigma, 2022)
The change of offline learning activities to online is a must during the pandemic. Based on this, this study aims to determine the implementation of virtual learning in training the creativity of students during the COVID-19 pandemic in the 2020/2021 school year at Birrul Walidain Kindergarten. This research method is descriptive qualitative. Data collection techniques using observation, interview and documentation techniques. The results showed that online learning in training creativity had been carried out well in accordance with the themes listed in the RPPH and RPPM. The online learning implementation technique uses the Zoom and Video Call applications with notification of information on equipment and learning materials the day before the lesson. Learning materials and equipment are distributed to children every two weeks, in addition to the preparation of tools and materials before the implementation of virtual learning in training the creativity of children, teachers use tutorial methods through videos and live demonstrations in front of a laptop screen that children can follow from home directly. on line. This is effective in training children's creativity in virtual learning because tools and materials are available in front of children during virtual learning and everything has been well facilitated by the institution. And the benefits of online learning are communication between educators, students and parents of students and become a means of reporting student progress.